MANAJEMEN INSIDEN CUSTOMER TELKOM BERBASIS SERVICE DESK MENGGUNAKAN FRAMEWORK ITIL V3 - Andira, Fransisca Ayu; Hadian, Nur; Hidayat, Husni (Information Technology Education Department, 2025)
In today's digital era, information technology (IT) plays an important role as the main support for business processes in various organizations, companies, and government agencies. Disruptions in IT services can have a serious impact on business operations, so effective IT service management is needed to improve service quality and stability. This research aims to identify gaps in IT incident management at PT Telekomunikasi Indonesia Merak Pekalongan City by applying the Information Technology Infrastructure Library (ITIL) version 3 framework which is an industry standard for Information Technology Service Management (ITSM). Research methods include interviews, observations, and literature studies, followed by a gap analysis between existing conditions and ideal conditions in handling IT incidents. The findings show that the current incident management process is reactive, without structured incident logging, and there is no standard escalation and resolution time. Based on the results of the gap analysis, this research produces a draft Standard Operating Procedure (SOP) that covers incident handling, escalation, incident closure, and recapitulation. This SOP aims to improve incident handling efficiency, speed up response time, and ensure better incident documentation. ITIL implementation is expected to improve IT service performance, reduce the impact of disruptions, and provide added value to customers. This research contributes to the development of more effective incident management procedures in organizations, particularly those operating in the telecommunications sector.